Niger, Guizotia abyssinica (L.f.) Cass. - Getinet, A.; Sharma, S.M.; Leibniz Institute of Plant Genetics and Crop Plant Research (1996)
Indigenous in Ethiopia where it is grown in rotation with cereals and pulses, niger (Guizotia abyssinica) is an important oilseed crop supplying 50% of Ethiopian oilseed production. It is also grown in India in marginal areas where it contributes a small but important part of oilseed production (3%). This monograph describes the genetic resources of niger and reviews various aspects of its taxonomy and nomenclature, botany, reproduction, evolution and domestication, uses, diversity and breeding. In addition, a full account of crop production areas, ecology, agronomy, pests and diseases, technology, limitations, prospects and research needs are considered. Three appendices are included presenting: (1) descriptors used to characterize and evaluate Ethiopian accessions; (2) current niger research efforts tabulating information under the headings: scientist, institute, country and research area; and (3) centres of crop research, breeding and genetic resources. (Abstract © CAB ABSTRACTS, CAB International)